REPRESENTASI EMOSI TOKOH UTAMA DALAM FILM SORE: ISTRI DARI MASA DEPAN PERSPEKTIF PSIKOLOGI SASTRA DAVID KRECH - Wahyu Mardaning Hardiyanti; Audrey Zafira Salma (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2026)
This research is motivated by the role of film as a medium that represents the emotional dynamics of characters, with a focus on the complex inner conflict in the film Sore: Wife from the Future from a literary psychology perspective. This research aims to analyze the representation of the main character's emotions based on David Krech's four classifications of emotions, namely basic emotions, sensory, self-assessment, and other people's emotions. The method used is qualitative with a literary psychology approach, using primary data sources in the form of films and secondary data from scientific references, with data in the form of dialogue, scenes and character expressions. Data collection was carried out through listening and note-taking techniques with purposive sampling, while data analysis used an interactive model which included reduction, presentation and drawing conclusions, and its validity was tested through theoretical triangulation. The research results found 18 emotional data which were divided into four classifications, namely basic emotions, sensory stimuli, self-assessment, and relationships with other people. Dominant emotions include anger, discomfort, as well as forms of love such as caring and attachment, which are influenced by conflict, sensory stimulation, and self-reflection.